2017
DOI: 10.2298/tsci160526226x
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of the combusition and emission performances of 2,5-dimethylfuran diesel blends on a diesel engine

Abstract: Experiments were carried out in a direct injection compression ignition engine fueled with diesel-dimethylfuran blends. The combustion and emission performances of diesel-dimethylfuran blends were investigated under various loads ranging from 0.13 to 1.13 MPa brake mean effective pressure, and a constant speed of 1800 rpm. Results indicate that diesel-dimethylfuran blends have different combustion performance and produce longer ignition delay and shorter combustion duration compared with pure diesel. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…The possibility of using 2,5-DMF as a diesel fuel additive has also been investigated [181][182][183][184][185][186][187][188][189][190]. Chen et al [181] studied the performance of 2,5-DMF blends with diesel in a a multi-cylinder CI engine at a volumetric percentage of 30%.…”
Section: Engine Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of using 2,5-DMF as a diesel fuel additive has also been investigated [181][182][183][184][185][186][187][188][189][190]. Chen et al [181] studied the performance of 2,5-DMF blends with diesel in a a multi-cylinder CI engine at a volumetric percentage of 30%.…”
Section: Engine Studiesmentioning
confidence: 99%
“…Adding 2,5-DMF to diesel was observed to generally reduce PM concentration. Moreover, the use of 2,5-DMF/diesel blends was observed to slightly increase the NO x emissions, brake thermal efficiency and brake specific fuel consumption compared with using pure diesel fuel [188]. The combustion and emissions of three oxygenated ring HCs considered as diesel additives, including 2,5-DMF, were studied in a single-cylinder diesel engine by Zheng et al [189].…”
Section: Engine Studiesmentioning
confidence: 99%
“…As aforementioned design scheme, PACA can be connected either to the secondary air holes or to the dilution air holes. Actuator position is considered as an important factor affecting combustor performance with plasma assistance [14]. The PAC tests with different actuator positions were carried out and compared to normal combustion results.…”
Section: Effect Of Actuator Positionmentioning
confidence: 99%
“…The authors recently investigated the emission and combustion of diesel-MF blends and diesel-DMF blends in a direct injection compression ignition (DICI) engine, and found that MF addition retarded the combustion phase of blended fuels and increased the brake thermal efficiency of diesel engine [14]. Diesel-MF or diesel-DMF [15] blending promoted NOx emissions but decreased soot emissions significantly. As for the unregulated emissions, diesel-DMF blending increased the acetaldehyde emissions, while the benzene and 1.3-butadiene emissions were reduced compared with pure diesel [16].…”
Section: Introductionmentioning
confidence: 99%